(3RhGL CHj GdYGU Hf GdQHjYs - (3GdebOSj GdLeGYjdj GdOeTbqj GdMfHdj, CHh eMeO, Jbj GdOjf, YHO GdZfj Hf YHO GdhGMO Hf Ydj Hf SQhQ, J (B600 (3g`s
(3ChdgG (B:s
(3HSe Gddg (B... (3GNHQfG GdMGaX GdGeGe CHh WGgQ CMeO Hf eMeO Hf CMeO GdSdaj GdCUaNGfj QMeg Gddg HKZQ GdEScfOQjI CfHG CHh GdMSf GdeHGQc Hf YHO GdLHGQ Hf GMeO Hf GdbGSe GdUjQaj aj ZjQ eQI (B...s
(3BNQgG (B:s
... (3abGd CeG HYO aGfj CfcMJ CHG GdYGU Hf GdQHjY aMOKfj aUObfj hEf aGWeI HVYI efj (B... (3dG JLJeY HfJ QShd Gddg hHfJ YOh Gddg YfO QLd hGMO CHOG bGd aJQc Ydj GdNWHI (B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdGYdGe (B4\34s
(3EjVGM Gdecfhf (B2\104s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJGQjNs